Analisis Nilai Tambah Microcrysatalline Cellulose dari ampas sagu Provinsi Riau - Jayalaksamana, Maghfirah; Puji Lestari, Ririn; Haryanto, Edo; Sekar Pembayun, Lintar (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2025)
Riau Province is the largest sago starch producer in Indonesia, contributing approximately 73% of the national production, yet it faces significant challenges regarding sago pith waste management which causes environmental pollution. This study aims to analyze the value-added potential of the agro-industrial processing of sago pith waste into pharmaceutical-grade Microcrystalline Cellulose (MCC) in the Kepulauan Meranti Regency, comparing its profitability against the sale of raw waste. The research employed the Hayami method to measure the value transformation from raw material to downstream products. The analysis results indicate that converting 6.667 kg of sago waste into 1 kg of MCC yields a substantial economic leap. The process generates a value-added of IDR 1,096,085 per kg of output with a value-added ratio reaching 53.11%. Specifically, the cost structure reveals that this industry is labor-intensive, with a labor income share of 41.03%, indicating a positive impact on local employment absorption. The company's profit is recorded at 31.93% of the product value. These findings confirm that the downstreaming of sago waste into MCC is not only financially feasible with high profitability but also strategically vital for the regional macro-economy. Developing this industry serves as a potential solution for import substitution of national pharmaceutical raw materials, increases farmer income through waste utilization, and creates a broad economic multiplier effect for community welfare in sago-producing regions.